2019
DOI: 10.5209/reve.62811
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativismo agroalimentario en Europa. Dimensión, gobernanza y análisis BCG de las sociedades cooperativas TOP25 de la UE-28 y TOP10 en España

Abstract: Resumen. Este trabajo tiene por objeto analizar la situación del cooperativismo agroalimentario en Europa, para identificar las estrategias comunes aparecidas en los escenarios europeos y analizar la dinámica hacia el futuro en este siglo XXI. Un pilar fundamental de este trabajo es, por un lado, analizar la dimensión y los modelos de sociedades cooperativas agroalimentarias europeas, por otro, el dinamismo y posición empresarial de las mismas, efectuando un análisis según la matriz portafolio del Boston Consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…These firms have considerable experience and, on average, have more than 6,000 members. The integration and size of cooperatives have been considered clear development factors in the literature (Gorgues et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These firms have considerable experience and, on average, have more than 6,000 members. The integration and size of cooperatives have been considered clear development factors in the literature (Gorgues et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, studies in agricultural sectors have shown that organizational size is an explanatory factor of greater profitability (Castillo and García, 2013). The predominant organizational structure in the olive oil sector is that of the cooperative, and size plays a particularly prominent role in the grasping of opportunities in the environment based on criteria of profitability, innovation adoption, and efficiency (Gorgues et al, 2019;Moyano and Fidalgo, 2001). Based on these arguments, the following proposition may be formulated:…”
Section: Proposition 1 the Top Manager's Ict Training Boosts The Orgmentioning
confidence: 99%
“…In this sense, authors such as Pavitt (2003) maintain that the organizations of greater antiquity can find greater difficulties in innovation, because they have adopted organizational and commercial automatisms that make them more reticent and, therefore, present a worse business performance (Cucculelli et al, 2014). Innovation and market orientation is an essential aspect of profitability in the agri-food sector (Gorgues et al, 2019). Similarly, it has also been noted that younger organizations are more prone to innovation and better adaptation to markets (Frenkel et al, 2001), which translates into better organizational practices and greater economic efficiency.…”
Section: Proposed Development Factors For the Tunisian Olive Sectormentioning
confidence: 99%
“…La percepción de los grupos de interés externos es de vital importancia para diferenciar a la cooperativa en su entorno Colom et al (2019), MERCO (2018), Olmedo y Martínez (2011), Schwaiger (2004, Wessels (2003), Fombrun et al (2000) Fuente: Elaboración propia _____________ 6 Concretamente, este ranking relaciona la relevancia de las cooperativas con su nivel de ventas y empleados, dejando fuera aspectos importantes a tratar en la valoración de la reputación cooperativa. Disponible en: https://www.faecta.coop/fileadmin/documentos/nacional/RANKING_DE_EMPRESAS_MAS_RELEVANTES_DE_LA_ES_2016-2017_001.pdf (acceso octubre 2019).…”
Section: Admiración Y Respetounclassified